PLASTINATION TECHNIQUE FOR MUSEUM SPECIMENS - Siddiqui, M.A.; Akbar, M.; Rana, M.W. (Journal of Ayub Medical College Abbottabad, 1988)
Abstract: The museum specimens are commonly stored in formalin solution and create problems like transportation shrinkage and discoloration of the specimens. Formalin irritates sensitive mucous membranes and irritates aller gic reactions in the skin. To overcome these difficulties a new technique of Plastination of Dr. Gunther Van Hagens has been followed to check the suitability of the procedure and to introduce it in Pakistan. It is concluded that the procedure is simple, easily reproducible and only worthwhile if practiced regularly.